Study of biofilm formation among uropathogens isolated from catheter-associated UTI patient from a tertiary care hospital - Retina Paul,; Saha, Priyanka; Kuhu Pal,; Avi Kapoor,; Arpita Sinha,; Joydip Roy, (Asian Journal of Medical Sciences, 2024)
Background: Catheter-associated urinary tract infection (CAUTI) is a serious health threat and challenging infection. CAUTI accounts for up to 40% of all nosocomial infections. Biofilm provides a survival strategy to microorganisms and ultimately leads to re-infections and recurrence of urinary tract infections (UTI) despite a full course of antibiotics. Aims and Objectives: The present study was conducted to determine the prevalence of CAUTI in suspected UTI patients and prevalence of biofilm-forming uropathogens among CAUTI patients. Materials and Methods: The cross-sectional study was done over a period of 6 months among 95 catheterized CAUTI patients. Biofilm production among isolated uropathogens was tested by tissue culture plate, tube test, and congo red agar method. Isolates were identified as biofilm producer if they were tested positive by any one of the all four methods, and isolates were considered biofilm non-producer in consensus with all four methods. Results: In this study, the prevalence of CAUTI was 68.42%. Among 65 isolates most common uropathogen was 28 (43.07%) Escherichia coli. In this present study, the prevalence of biofilm-forming uropathogens was 58.46% (38). Tissue culture plate was the most sensitive (97.36%) method in detecting biofilm formation followed by modified congo red agar (82.21%), congo red agar (71.05%), and tube test (65.78%). Biofilm productions were significantly associated with female gender, diabetes, and prolonged catheterization. Conclusion: Indwelling urinary catheter acts as a nidus for biofilm formation among microorganisms. Duration of catheterization is inversely associated with UTI. Hence, the need for catheter removal should be assessed daily to prevent infection. Periodic surveillance should be done to detect biofilm formation where prolonged catheterization is inevitable.